If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -7) = 2(2 + -2x) + -3 Reorder the terms: 5(-7 + x) = 2(2 + -2x) + -3 (-7 * 5 + x * 5) = 2(2 + -2x) + -3 (-35 + 5x) = 2(2 + -2x) + -3 -35 + 5x = (2 * 2 + -2x * 2) + -3 -35 + 5x = (4 + -4x) + -3 Reorder the terms: -35 + 5x = 4 + -3 + -4x Combine like terms: 4 + -3 = 1 -35 + 5x = 1 + -4x Solving -35 + 5x = 1 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -35 + 5x + 4x = 1 + -4x + 4x Combine like terms: 5x + 4x = 9x -35 + 9x = 1 + -4x + 4x Combine like terms: -4x + 4x = 0 -35 + 9x = 1 + 0 -35 + 9x = 1 Add '35' to each side of the equation. -35 + 35 + 9x = 1 + 35 Combine like terms: -35 + 35 = 0 0 + 9x = 1 + 35 9x = 1 + 35 Combine like terms: 1 + 35 = 36 9x = 36 Divide each side by '9'. x = 4 Simplifying x = 4
| [9(x+5)-16]+[3(x-2)+4]= | | x+8-1/3=90/11 | | 2x^2+8x-192=0 | | 3x+(x*x)=180 | | 0.06(10-x)(100)= | | x^2-5x=x(5+x) | | x^2-5x=x(5x) | | 2x+55=272 | | (4y-7)+(-2y+5)= | | 2/5(x+3)=6 | | 3x+7-8(x+2)=-36 | | N(N-3)=700 | | 23-4x=9 | | 16x^4-54x= | | 9w-28=2 | | 4a-4=4x+4-2x | | 4t^2-16t+7=0 | | x^7+64x^4=0 | | 3y^2+17y-28= | | 6a+a-9=30 | | 7-5a=17 | | 2(4a+3)=8+6(2a-3) | | 8x-32=-8(4-5x) | | 7(3x-4)=59 | | 3x+-4=14 | | 2y+50+5y-17=180 | | 3[5(z-5)+17]-[3(5z-3)+3]= | | -(8*m+4)=4*m-2(6*m+2) | | 7x+4=8+2x | | -3x+7=4 | | 5x-(2x+3)=4(x+1)-2 | | 4t^2-16t+15=0 |